What kinds of government trust structures affect political participation? Evidence from Chinese Youth Netizens - Cheng Wen; Qian Hu; Sheng Chen (PLoS ONE, 2025)
Based on 2018 research data on Chinese netizens’ social awareness, this paper examines how different government trust structures influence youth netizens’ political participation. The findings indicate that the reinforcing effect of government trust on political participation follows a declining order: paradoxical government trust, equal trust, hierarchical government trust, and equal distrust. In this context, subjective well-being is introduced as a mediating variable. The results show that the positive impact of subjective well-being on political participation varies across different trust structures, decreasing in the following order: equal trust holders, paradoxical government trust holders, hierarchical government trust holders, and equal distrust holders. Furthermore, heterogeneity analysis reveals that the negative impact of equal distrust and hierarchical government trust is weaker on online political participation than on offline political participation, while paradoxical government trust has a stronger positive effect online than offline. Overall, the influence of government trust structure is weaker for online political participation than for offline political participation.